Mary Heaton Vorse The Life of an American Insurgent - Garrison, Dee (Temple University Press, 1989)
The life of Mary Heaton Vorse (1874-1966) reads like a chronology of American radicalism in the first half of the twentieth century. The foremost pioneer of labor journalism in the U.S. and a prominent participant in the women's universal suffrage movement, Vorse spent her life actively struggling for libertarian socialism, feminism, and world peace. Her friends and colleagues were among the most famous writers, artists, and intellectuals of the time. Her sizeable FBI file was maintained until she was eighty-two years old. This compelling biography restores an important heroine to her place in American and feminist history.